Effectiveness of educational interventions for adults living with Type 2 Diabetes Mellitus in Nigeria: A systematic review of original research - NA Abdulmalik; OA AKPOR; OA ADEOLUWA; KS Olaniyi; Adetunji Dayo Atimiwoaye (Babcock University Medical Journal, 2025)
Background: Educational interventions have been recognized as an effective strategy for improving diabetes management outcomes, but their effectiveness in the Nigerian context has not been systematically reviewed. This systematic review evaluates the effectiveness of educational interventions for adults with T2DM in Nigeria, focusing on clinical, behavioral, and psychosocial outcomes. It also highlights the cultural relevance, barriers, and facilitators of these interventions.